The Southwestern Mandarin /n/-/l/ Merger: Effects on Production in Standard Mandarin and English - Zhang, Wei; Levis, John M. (Frontiers in Communication, 2021)
Southwestern Mandarin is one of the most important modern Chinese dialects, with over 270 million speakers. One of its most noticeable phonological features is an inconsistent distinction between the pronunciation of [n] and [l], a feature shared with Cantonese. However, while /n/-/l/ in Cantonese has been studied extensively, especially in its effect upon English pronunciation, the /l/-/n/ distinction has not been widely studied for Southwestern Mandarin speakers. Many speakers of Southwestern Mandarin learn Standard Mandarin as a second language when they begin formal schooling, and English as a third language later. Their lack of /l/-/n/ distinction is largely a marker of regional accent. In English, however, the lack of a distinction risks loss of intelligibility because of the high functional load of /l/-/n/. This study is a phonetic investigation of initial and medial [n] and [l] production in English and Standard Mandarin by speakers of Southwestern Mandarin. Our goal is to identify how Southwestern Mandarin speakers produce [n] and [l] in their additional languages, thus providing evidence for variations within Southwestern Mandarin and identifying likely difficulties for L2 learning. Twenty-five Southwestern Mandarin speakers recorded English words with word initial [n] and [l], medial ll or nn spellings (e.g., swallow, winner), and word-medial [nl] combinations (e.g., only) and [ln] combinations (e.g., walnut). They also read Standard Mandarin monosyllabic words with initial [l] and [n], and Standard Mandarin disyllabic words with [l] or [n]. Of the 25 subjects, 18 showed difficulties producing [n] and [l] consistently where required, while seven (all part of the same regional variety) showed no such difficulty. The results indicate that SWM speakers had more difficulty with initial nasal sounds in Standard Mandarin, which was similar to their performance in producing Standard Mandarin monosyllabic words. For English, production of [l] was significantly less accurate than [n], and [l] production in English was significantly worse than in Standard Mandarin. When both sounds occurred next to each other, there was a tendency toward producing only one sound, suggesting that the speakers assimilated production toward one phonological target. The results suggest that L1 influence may differ for the L2 and L3.